Analisis Kinerja Realisasi Anggaran Pendapatan Belanja Daerah Pada Badan Keuangan Aset Daerah Pemerintah Kota Medan - Muhammad Arief Pramusty; Nur Fadhilah Ahmad Hasibuan (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2023)
This study describes and explains the budget realization for the last five years, starting from 2018 to 2022, by paying attention to the percentage change between the budget value and the realization of the regional income and expenditure budget each year. The purpose of this study is to evaluate the performance of regional revenue and expenditure budget realization in the regional asset finance agency of the Medan City government during the 2018-2022 period. This study also aims to compare the effectiveness of budget realization during that period. The research method used is descriptive qualitative using secondary data sources and documentation study data collection techniques. Data analysis involves revenue variance analysis, degree of decentralization ratio, local tax effectiveness ratio analysis, and expenditure budget variance analysis. The results show a problem, where the realization of the regional revenue and expenditure budget in 2019-2020 has increased, even though it should have decreased due to the impact of the COVID-19 pandemic. This problem is related to the loss of funds worth 1.6 million which has been handled by Law Enforcement Officials.